THE EFFECT OF FINANCIAL RATIO ON PROFIT GROWTH IN FOOD AND BEVERAGE COMPANIES IN IDX - Kharisma Aulia Dianitha; Endang Masitoh; Purnama Siddi (Universitas Airlangga, 2020)
This study aims to examine and analyze the effect of Quick Ratio, Debt to Equity Ratio, Net Profit Margin, and Return On Investment on Profit Growth in Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2015 – 2018. The sample in this study was 12 samples. The method of data analysis in this study is multiple linear regression analysis. The results of this study indicate that the quick ratio, debt to equity ratio, net profit margin, and return on investment simultaneously affect profit growth with a value of sig <0.05. Partially, only return on investment has an effect on profit growth with a value of sig. 0.009 which means less than <0.05.